META SYNTHESIS: MATHEMATICAL LITERACY REVIEWED FROM GENDER IN JUNIOR HIGH SCHOOL STUDENTS - Raharani, Fatkhiya An-Nisa; Junaedi, Iwan; Dewi, Nuriana Rachmani (Prima: Jurnal Pendidikan Matematika, 2024)
Have good mathematical literacy is important to develop because it plays an important role in solving various problems in everyday life. Meanwhile, the mathematical literacy of male and female students is different. This study aims to see and describe how mathematical literacy differences in male and female students at the junior high school level. The method used in research is meta-synthesis which is carried out by analyzing qualitative data derived from various similar studies. As a result, male students have a tendency to have better mathematical literacy than female students. Of the seven indicators of mathematical literacy, male students are able to master four to seven indicators. Meanwhile, female students can only meet three to seven indicators. Male and female students have equally fulfilled communication, mathematization, and representation skills. Both also need to improve their ability to determine problem-solving strategies and provide logical reasoning and reasoning. Furthermore, the authors suggest that similar research be carried out with a longer time span and a wider range of research areas. Furthermore, it can also conduct research on high school students so that they can be compared so that it can be understood whether there are significant differences in mathematical literacy skills at both school levels. Thus, the results obtained can be represented to be used as a basis for making decisions such as the development of more inclusive and effective learning strategies in the educational environment.